Perbandingan Efektifitas Ekstrak Daun Kelor (Moringa oleifera L.) dan Buah Bit (Beta vulgaris L.) Dalam Meningkatkan Kadar Hemoglobin (Hb) Pada Remaja Putri Dengan Anemia - Isy Royhanaty; Novi Anding Suciati; Yuli (Journal of Health (JoH), 2023)
Adolescent girls are at high risk of suffering from anemia, because there is an increase in iron needs due to growth and menstruation. The normal limit for hemoglobin levels for adolescent girls is 12 g/dl. Natural supplementation that has an anti-anemia effect, namely Moringa Leaf Extract (Moringa oleifera L.) and Bit Fruit Extract (Beta vulgaris L.), so that it can be used as an alternative to non-pharmacological therapy in increasing Hb levels. Research Objectives is to determine the difference in the effectiveness of Moringa leaf extract and beet fruit extract on increasing Hb levels in adolescent girls at SMK Muhammadiyah I Pemalang. The type of research is Quasi Experiment, with a two group pre-test-post-test design. The sampling technique in this study used purposive sampling. The statistical test used is the Man Whitney U. Results: Moringa leaf extract (mean rank 27,50) was more effective than beet fruit extract (mean rank 9,50) in increasing Hb levels. Mann_Whitney U test obtained p value 0.000 < 0.05, which means that there are differences in effectiveness in the two intervention groups. There is a difference in effectiveness between Moringa leaf extract and beet fruit extract on increasing Hb levels in adolescent girls at SMK Muhammadiyah I Pemalang with a p value of 0.000. Moringa leaf extract is more effective than beet fruit extract in increasing Hb levels. Moringa leaf extract and beet fruit extract can be used as non-pharmacological therapy in increasing hemoglobin level.